Role of carbon nanotube ribbon on the superconducting properties of epitaxial NbC films - Zhang, Yingying (2012)
We demonstrated the integration of highly aligned carbon nanotube (CNT) ribbons with epitaxial NbC films. The formation of NbC/CNT composites enhanced the normal-state conductivity along the CNT axial direction and improved the superconducting transition temperature of the assembly. The enhanced upper critical field of NbC/CNT suggested that the inclusion of CNTs in the NbC matrix reduced the coherence length of the NbC. Nanomechanical testing also demonstrated the potential for enhanced fracture toughness of NbC/CNT composites.